PHYSICAL QUALITY OF ELEPHANT GRASS (Pennisetum purpureum) SILAGE WITH DIFFERENT LEVELS OF Gliricidia sepium LEAF MEAL ADDITION - A. M., Ardani; Cakra, I. G. L. O.; Trisnadewi, A. A. A. S. (Jurnal Peternakan Tropika, 2024)
This study aimed to determine the effect of adding Gliricidia sepium (G. sepium) leaf meal to the physical quality of elephant grass (Pennisetum purpureum) silage. This research was conducted at Sesetan Research Station on Jalan Raya Sesetan Gang Markisa and Nutrition and Animal Feed Laboratory, Faculty of Animal Husbandry, Udayana University. This study conducted for one month, using a completely randomized design consisting of four treatments and five replications. The treatments consisted of P1 (95% elephant grass + 0% G. sepium leaf meal + 5% molases), P2 (85% elephant grass + 10% G. sepium leaf meal + 5% molases) P3 (75% elephant grass + 20% G. sepium leaf meal + 5% molases), and P4 (65% elephant grass + 30% G. sepium leaf meal + 5% molases). The variables observed were color, odor, texture, presence of fungi and pH value of silage. pH value data were analyzed with analysis of variance and physical quality data were analyzed using a frequency distribution. The results of the research on the silage color variable P1 got the highest physical quality test value, on the silage texture variable P2 got the highest physical quality test, on the silage smell variable P1 got the highest physical quality test, on the presence of fungi variable P3 got the highest physical quality test, and on the variable The pH of silage P1, P2, P3, P4 obtained good pH values. The conclusion of this study is that the addition of G. sepium leaf meal to silage has not produced good physical quality of silage compared to silage without the addition of G. sepium leaf meal, and the physical quality of silage without the addition of G. sepium leaf meal has the best physical quality of silage.